The The Effect of Cash on Delivery, Online Consumer Rating and Reviews on the Online Product Purchase Decisions - Dayat Ikhsan Hajati (Entrepreneurship Faculty, Universitas Garut, 2022)
Abstract– The aims of the study were to analyze the factors that influence the online purchase decision, such as cash on delivery service, consumer online rating, and review. This study took 100 samples by using the accidental sampling technique. The data analysis technique used in this study was descriptive statistical analysis and multiple linear regression analysis. The study results showed that 1) there was a significant and positive effect of cash on delivery service on the online purchase decision partially, 2) consumer online rating and review had a significant and positive effect on the online purchase decision partially, 3) there was the significant and positive effect of cash on delivery service, consumer online rating, and review on the online purchase decision simultaneously.